Photoinduced dynamics to photoluminescence in Ln3+ (Ln = Ce, Pr) doped β-NaYF4 nanocrystals computed in basis of non-collinear spin DFT with spin-orbit coupling. (19th March 2018) - Han, Yulun; Vogel, Dayton J.; Inerbaev, Talgat M.; May, P. Stanley; Berry, Mary T.; Kilin, Dmitri S.
ABSTRACT: In this work, non-collinear spin DFT + U approaches with spin-orbit coupling (SOC) are applied to Ln 3+ doped β-NaYF4 (Ln = Ce, Pr) nanocrystals in Vienna ab initio Simulation Package taking into account unpaired spin configurations using the Perdew–Burke–Ernzerhof functional in a plane wave basis set. The calculated absorption spectra from non-collinear spin DFT + U approaches are compared with that from spin-polarised DFT + U approaches. The spectral difference indicates the importance of spin–flip transitions of Ln 3+ ions. Suite of codes for nonadiabatic dynamics has been developed for 2-component spinor orbitals. On-the-fly nonadiabatic coupling calculations provide transition probabilities facilitated by nuclear motion. Relaxation rates of electrons and holes are calculated using Redfield theory in the reduced density matrix formalism cast in the basis of non-collinear spin DFT + U with SOC. The emission spectra are calculated using the time-integrated method along the excited state trajectories based on nonadiabatic couplings. Abstract :